Aplicação da geoengenharia como ferramenta para controle de florações de algas e da fertilização interna de fósforo em um ecossistema aquático eutrofizado - Jose Neuciano Pinheiro de Oliveira (2017)
Eutrophication is considered a serious problem of freshwater systems caused by the enrichment of water by nutrients, typically phosphorus and nitrogen, resulting in increase of primary production and blooms of algae and cyanobacteria. In this sense, the development of innovative lake restoration techniques, such as geoengineering, has become a promising tool to reduce the internal P loading and to control eutrophication in freshwaters. The aim of this study was to evaluate the application of geoengineering techniques for the control of algal blooms and internal P loading in a eutrophic ecosystem located in the tropical semiarid region. The experiments were carried out with water from the Gargalheiras reservoir, located in the semiarid region of the state of Rio Grande do Norte, Brazil. The first experiments consisted of phosphate adsorption tests by natural bentonite clay (BEN) and lanthanum modified bentonite clay (LMB). Other experiments consisted in tests to evaluate the flocculation and sedimentation of algal biomass and phosphorus with the application of flocculants polyaluminium chloride (PAC) and aluminum sulphate (Al2SO4) flocculants isolated or combined with the ballasts natural bentonite clay (BEN) and lanthanum-modified bentonite clay (LMB). Sediment capping experiments were carried out with application of LMB isolated or in combination with PAC or Al2SO4 using selected doses according to the P loads present in the water and the sediment of the reservoir. For the P adsorption tests by the LMB and BEN clays it was observed that the maximum capacities of phosphate adsorption by natural and lanthanum-modified bentonite clays are considerably reduced in natural waters with physicochemical characteristics that interfere with the adsorption process, such as the presence of humic substances associated with a high pH. The results of the flocculation and sedimentation tests showed that the isolated application of the flocculants had the same effect in the removal of algal biomass and total phosphorus in relation to those treatments with a combination of these agents with the clays, resulting in mesotrophic conditions (Chl-a <12 g.L-1; Total P <60 g.L-1) and being effective for a control of eutrophication in the Gargalheiras reservoir. Finally, the sediment capping experiments showed that the isolated application of the LMB in the dose of 100 g LMB: 1 g P is effective in the control of internal P loading of Gargalheiras reservoir under aerobic conditions and with pH ranging from 6 and 8. It was also observed that the use of LMB combined with low doses of the flocculants Al2SO4 and PAC does not present advantages in relation to the control of the internal P loading carried out by LMB solely. In conclusion, the application of geoengineering techniques used in this study were efficient in the removal of algal biomass and total phosphorus from the water column of the Gargalheiras reservoir, presenting high performance in the immobilization of P in the sediment and control of internal P loading